(3GdahGFO GdeQVjI aj TQM GdedbHGJ GdaQVjI GdhQOjIs - (3YHO Gddg Hf HgGA GdOjf GdTfThQj GdTGaYj GdaQVis; (3GHf GdhQOj , YeQ Hf eXaQ Hf YeQ Hf eMeO GHf CHj GdahGQS GdeYQj GdcfOj, Rjf GdOjf CHh MaU,J (B749 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd GdabjQ YHOGddg Gddg Hf GdTjN HgGA GdOjf dGJSYfi eNGdaJg Cf CTQM GdedbHGJ GdhQOjI s
(3BNQgG (B:s
(3hcKjQ ef GdVYaI jHGOQ bHd PcQ GdaJhi Edi GeaGUjd hGdJUMjM ajfHZi ELJfGH Pdc hGddg CYde GfJgi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGGH GdKGfis
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B228 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B3s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B553s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Yde GdaQGFVs